2023
DOI: 10.1111/jcmm.17835
|View full text |Cite
|
Sign up to set email alerts
|

MALAT1/miR‐185‐5p mediated high glucose‐induced oxidative stress, mitochondrial injury and cardiomyocyte apoptosis via the RhoA/ROCK pathway

Abstract: To explore the underlying mechanism of lncRNA MALAT1 in the pathogenesis of diabetic cardiomyopathy (DCM). DCM models were confirmed in db/db mice. MiRNAs in myocardium were detected by miRNA sequencing. The interactions of miR‐185‐5p with MALAT1 and RhoA were validated by dual‐luciferase reporter assays. Primary neonatal cardiomyocytes were cultured with 5.5 or 30 mmol/L D‐glucose (HG) in the presence or absence of MALAT1‐shRNA and fasudil, a ROCK inhibitor. MALAT1 and miR‐185‐5p expression were determined by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…Liu et al suggest that down-regulated NORAD improves cardiac fibrosis in db/db mice via the NORAD/miR-125a-3p/Fyn axis [ 38 ]. In our previous study, we found that lncRNA MALAT1 expression was elevated in HG-induced primary mouse cardiomyocytes and mediated HG-induced apoptosis through activation of the RhoA/ROCK pathway via sponging miR-185-5p [ 39 ]. This is consistent with our present results, our RNA-sequencing results showed a trend of increased expression of MALAT1 in DCM group and our data also revealed reduced Bcl-2 expression and elevated Bax expression in db/db mice hearts, which demonstrating a trend toward increased apoptosis in DCM.…”
Section: Discussionmentioning
confidence: 99%
“…Liu et al suggest that down-regulated NORAD improves cardiac fibrosis in db/db mice via the NORAD/miR-125a-3p/Fyn axis [ 38 ]. In our previous study, we found that lncRNA MALAT1 expression was elevated in HG-induced primary mouse cardiomyocytes and mediated HG-induced apoptosis through activation of the RhoA/ROCK pathway via sponging miR-185-5p [ 39 ]. This is consistent with our present results, our RNA-sequencing results showed a trend of increased expression of MALAT1 in DCM group and our data also revealed reduced Bcl-2 expression and elevated Bax expression in db/db mice hearts, which demonstrating a trend toward increased apoptosis in DCM.…”
Section: Discussionmentioning
confidence: 99%
“…Knockdown of HOTAIR in high glucose-induced H9c2 cells resulted in increased oxidative injury. HOTAIR could protect against DCM via activating of the Sirtuin 1(SIRT1) expression by sponging miR-34a [ 90 ]. Additionally, lncRNA MALAT1 was significantly upregulated in the myocardium of diabetic mice and high glucose-induced cardiomyocytes, mediated oxidative stress, mitochondrial damage and apoptosis through activating the RhoA/ROCK pathway via sponging miR-185-5p.…”
Section: Lncrnasmentioning
confidence: 99%